Integritas Banser Kabupaten Nganjuk Dalam Prinsip NKRI Harga Mati: Sebuah Perspektif Cultural Theory - Arif, Muhammad; Darwati, Yuli (Bahasa Indonesia, 2022)
Abstrak Banser is a semi-autonomous body of the Ansor Youth Movement of the largest mass organization in Indonesia, namely Nahdlatul Ulama'. Banser has a field of assignments related to the field of social religion which is more practical and strategic. Regeneration in Ansor and Banser bodies is held every week, and continues to be ongoing in order to prepare new cadres. Regeneration must be carried out actively and programmed in accordance with the vision and mission that has been set. Distribution and independence continues to be carried out in stages. This vision and mission will continue to be realized over the next few years in order to form massive integrity and make a major contribution to all Indonesian people. So that a principle can be formed that is very strongly internalized within Banser's body, namely "NKRI Harga Mati". In accordance with the social conditions in Nganjuk Regency, the research carries the theme of integrity in the principle of the Unitary State of the Republic of Indonesia. The research was carried out using qualitative methods in a case study approach. This approach was chosen because the object of study is a system, so case studies were chosen as an alternative to describe the phenomena that arise. The data purification process was carried out using observation, interview, and recording methods by checking the validity of the data using triangulation. Cultural Theory was chosen as the analytical knife in positioning the Banser problem in response to the era of globalization and the challenges of the times with the principle of the Unitary Republic of Indonesia at Dead Price.